2019
DOI: 10.1007/s00605-019-01281-x
|View full text |Cite
|
Sign up to set email alerts
|

On preservation of automatic continuity

Abstract: A group G is called automatically continuous if any homomorphism from a completely metrizable or locally compact Hausdorff group to G has open kernel. In this paper, we study preservation of automatic continuity under group-theoretic constructions, focusing mainly on groups of size less than continuum. In particular, we consider group extensions and graph products. As a consequence, we establish automatic continuity of virtually poly-free groups, and hence of non-exceptional spherical Artin groups.On the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…It is known that a rightangled Artin group A acts freely on the universal cover of the corresponding Salvetti complex S which is a finite dimensional CAT.0/ cube complex [13,Theorem 3.6]. Hence, as an immediate application of Proposition C we obtain a geometric proof for the following result, which can be proved by using Dudley's arguments in [18] and can be found in [16,Corollary 3.13].…”
Section: Introductionmentioning
confidence: 88%
“…It is known that a rightangled Artin group A acts freely on the universal cover of the corresponding Salvetti complex S which is a finite dimensional CAT.0/ cube complex [13,Theorem 3.6]. Hence, as an immediate application of Proposition C we obtain a geometric proof for the following result, which can be proved by using Dudley's arguments in [18] and can be found in [16,Corollary 3.13].…”
Section: Introductionmentioning
confidence: 88%
“…Free (abelian) groups were classically shown to be cm-slender, lcH-slender and n-slender (see [23] and [34]). More recent work has shown that torsion-free word hyperbolic groups, right-angled Artin groups, braid groups and many other groups satisfy various of these slenderness conditions (see [17,20,39,44]). Note that a group which is either n-slender, cm-slender, or lccH-slender must be torsion-free.…”
Section: Problem 1 Does There Exist a Finitely Generated (Countable) Torsion-free Acylindrically Hyperbolic Group Which Does Not Admit Unmentioning
confidence: 99%
“…Another important result in this direction is a theorem of Nikolov and Segal [45, Theorem 1.1], which says that every abstract homomorphism from a finitely generated in topological sense profinite group to any profinite group is continuous. Papers [14,17,20,23,39,43,49] deal with automatic continuity of abstract homomorphisms from locally compact Hausdorff groups to some discrete groups; papers [17,20] also deal with completely metrizable groups as domains.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that many interesting groups, including free groups, free abelian groups and torsion-free word-hyperbolic groups, are lch-slender and cmslender and that for abelian groups we recover the usual slender groups. Several types and properties of automatically continuous were studied in [10,24]. Most recently, Corson and Varghese [11] strengthened the connection between slender groups and automatic continuity by showing that a group is lch-slender if it is torsion-free and it does not contain Q or p-adic integers for any p.…”
Section: Introductionmentioning
confidence: 99%